2010
DOI: 10.1002/job.684
|View full text |Cite
|
Sign up to set email alerts
|

Balancing cognition and emotion: Innovation implementation as a function of cognitive appraisal and emotional reactions toward innovation

Abstract: SummaryFocusing on the role of emotions in understanding employee behavior, the present study identifies employees' emotional reactions toward innovation as a mediating process that explains the effects of institutional environment on collective innovation use in work units. We further employed the appraisal theory of emotion and affective events theory (AET) to conceptualize the relationships between cognitions and emotions involving innovation. This expanded conceptual model was tested using multi-source dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 49 publications
7
88
0
9
Order By: Relevance
“…The authors concluded that these findings provided further support to the importance of social processes and relationships to team level innovation (e.g., Perry-Smith & Shalley, 2003) as well as the importance of team climate and group process to effective innovativeness within work teams (Choi et al, 2011;Pirola-Merlo & Mann, 2004;Zhang et al, 2007).…”
Section: Team Level Studiesmentioning
confidence: 86%
“…The authors concluded that these findings provided further support to the importance of social processes and relationships to team level innovation (e.g., Perry-Smith & Shalley, 2003) as well as the importance of team climate and group process to effective innovativeness within work teams (Choi et al, 2011;Pirola-Merlo & Mann, 2004;Zhang et al, 2007).…”
Section: Team Level Studiesmentioning
confidence: 86%
“…They suggest that, before using the innovation, any threats to expected goals were only hypothetical, which possibly means that the negative emotions generated before the use were not substantial enough to influence evaluations. Choi, et al [54] highlight the important role of emotions in the context of innovation adoption within an organization. They suggest that overall positive emotions toward an innovation are positively related to the effectiveness of its implementation.…”
Section: Positive Emotionsmentioning
confidence: 99%
“…Furthermore, the literature reports that human behaviour is affected not only by cognitive processes, but also by affective processes (Brief and Weiss, 2002;Choi et al, 2011; Koenig-Lewis et al, 2014; Nyer, 1997). As well as understanding residents' judgments of the phenomenon studied, it is also essential to understand their affective responses in order to fully appreciate how their daily experiences and well-being are shaped (Atari et al, 2011;Davidson and Milligan, 2004).…”
mentioning
confidence: 99%